Pertumbuhan Akar dan Produktivitas Tanaman Tomat (Solanum lycopersium L.) dengan Variasi Ukuran Media Tanam Hydroton - Alwi, Ivo Ali Saifullah; Tusi, Ahmad; Oktafri, Oktafri; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2022)
Hydroton is a clay-based growing medium used in hydroponic systems with variations in size 1-2.5 cm. In Indonesia, most hydrotons are still imported from other countries. The main purpose of this study was to observe the root growth and production of tomato plants grown on hydroponic systems, static aerated technique (SAT) with variations in hydroton size. This study was designed using a complete random design (CRD) with 4 hydroton size treatments (commercial hydroton as control (H0) and 3 experimental treatment with differences in hydroton size made from a mixture of clay and charcoal husk burn (H1, H2 and H3) and 6 replications in each size treatment so that there are 24 experimental units. On the observation of plant productivity showed different results on the treatment applied, while on the growth of roots did not show different results but the growth of roots on artificial hydroton better than commercial hydroton as a control based on physical roots and trend data. The amount of fruit harvested per plant obtained the best results of 25 fruits in the H3 treatment and the total weight of fruit per plant obtained the best results of 1.055,5 grams in the H3 treatment. The longest root in this study measured 96.6 cm in H0 treatment and the weight of the heaviest root in the net pot is 71,5 grams in H1 treatment while the weight of the heaviest root outside the net pot is 276,6 grams in H2 treatment. Based on the results of this study, the increase in the size of the hydroton is able to increase the production value of tomato plants compared to commercial hydroton and hydroton which are smaller in size.